Research on Fluid Viscous Damper Parameters of Cable-Stayed Bridge in Northwest China - Xiongjun He; Yongchao Yang; Xiang Xiao; Yulin Deng (Shock and Vibration)
To optimize the aseismic performance of nonlinear fluid viscous dampers (FVD) of cable-stayed bridge in the highly seismic zone, Xigu Yellow River Bridge in northwest China is taken as an example. Nonlinear time-history analysis method is used to research on the relation among the internal forces, displacements, and damping parameters of the 650 tonnage FVD. The method of getting the minimum of binary functions is used to obtain the optimal parameters of FVD. Also, the 1 : 1 full-scale FVD model is made and used in the constitutive relation test. Then the test result of the damping parameters can be got by normal equation method. The optimized method to obtain the damping parameters is further verified. The results indicate that seismic response in key positions of the cable-stayed bridge can be reduced by installing longitudinal nonlinear FVD between the towers and girders if choosing reasonable damping parameters C and ξ. The optimal damping parameters can be calculated accurately by the proposed method of optimizing damping parameters of nonlinear FVD, and the constitutive relation test verifies the correctness of the optimization analysis method. Conclusions concerned can be applied to the design of nonlinear FVD for cable-stayed bridges.